Evaluation of the antioxidant activity of Berberis jaeschkeana C. K. Schneid. fruits using the ABTS assay - Och, Anna; Ćwikła, Agata; Orzechowska, Karolina; Cwener, Anna (Publishing Office of the University of Rzeszow, 2023)
Introduction and aim. The assessment of the antioxidant activity of plant extracts is an important research direction in the search for new chemopreventive substances. The aim of this study was to demonstrate the antioxidant potential of the methanol extract of Berberis jaeschkeana C. K. Schneid fruit. Material and methods. Spectrophotometric tests were carried out: testing of the total content of polyphenols (TPC) in extracts, testing of the total content of flavonoids (TFC) in extracts. Antiradical activity was determined using the improved ABTS+• decolorization test with modifications. Results. TPC extracts was determined at the level of 43.52±2.37 mg/g, while TFC extracts was determined at the level 6.08±0.48 mg/g. The ABTS activity test showed 31.15 mg/g expressed as mg Trolox per g of dry extract. Conclusion. It was assessed that the methanolic extract of the fruit of Berberis jaeschkeana C. K. Schneid. has an antioxidant properties, what makes it a potential chemopreventive agent in civilizational diseases.
Keywords: antioxidants; Berberis jaeschkeana C. K. Schneid.; chemoprevention; civilization disease; fruit extract; traditional medicine